2008
DOI: 10.1055/s-2008-1078693
|View full text |Cite
|
Sign up to set email alerts
|

Specific Complications Associated with Different Types of Intrinsic Pedicle Flaps of the Hand

Abstract: One hundred eight pedicle flaps intrinsic to the hand were performed in 98 male and 10 female patients averaging 36 years of age for digit-level trauma in 19 thumbs, 27 index, 50 long, 8 ring, and 4 small fingers. Specific flaps employed were 79 antegrade proper digital artery, 10 reverse proper digital artery, 6 reverse second dorsal metacarpal artery, 5 antegrade first dorsal metacarpal artery, 6 reverse dorsal ulnar artery of thumb, and 2 dorsal middle phalangeal flaps. The final average total active motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This left us unable to elucidate the complications specific to thumb reconstruction, thereby reducing the overall number of cases reviewed. 30 39 On evaluation of bias as per the criteria from the NIH quality assessment tool, only three studies had a high risk of bias. There was no uniformity on follow-up time, which varied from 3 to 46 months.…”
Section: Discussionmentioning
confidence: 99%
“…This left us unable to elucidate the complications specific to thumb reconstruction, thereby reducing the overall number of cases reviewed. 30 39 On evaluation of bias as per the criteria from the NIH quality assessment tool, only three studies had a high risk of bias. There was no uniformity on follow-up time, which varied from 3 to 46 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical use, one is bound to meet some problems even with the most reliable flaps. 7) Local flaps are most commonly performed to cover traumatic defects. Poor design of the flap or imperfect execution of the operation may result in unnecessary reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported a re-operation rate of 13.8% in a series of 108 pedicled flaps even after excluding VY-plasties. 7) The author state, that antegrade flow flaps suffered more often from partial ischemia and loss of the flap and retrograde flaps from venous congestions, but he did not declare the numbers to compare the number of re-operations of different flaps.…”
mentioning
confidence: 99%